2019
DOI: 10.1101/564211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of diet and weight on taste responses in diet-induced obese mice

Abstract: Objective Previous studies have reported that individuals with obesity have reduced taste perception, but the relationship between obesity and taste is poorly understood. Earlier work has demonstrated that diet‐induced obesity directly impairs taste. Currently, it is not clear whether these changes to taste are due to obesity or to the high‐fat diet exposure. The goal of the current study was to determine whether diet or excess weight is responsible for the taste deficits induced by diet‐induced obesity. Metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Our previous work showed that the hexosamine biosynthesis pathway enzyme O-GlcNAc transferase (OGT) acts in the Gr5a + neurons to mediate the effects of high dietary sugar on sweet taste (14); whether the interaction between OGT and PRC2 is what promotes the repressive activity of the latter in these sensory neurons is a question worth investigating. Notably, the dysregulation of Polycomb-associated chromatin has been found in mice and humans with diet-induced obesity (50,51), suggesting that the mechanisms we found here could also underlie the chemosensory alterations reported in mammals (8)(9)(10)(11)(12).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our previous work showed that the hexosamine biosynthesis pathway enzyme O-GlcNAc transferase (OGT) acts in the Gr5a + neurons to mediate the effects of high dietary sugar on sweet taste (14); whether the interaction between OGT and PRC2 is what promotes the repressive activity of the latter in these sensory neurons is a question worth investigating. Notably, the dysregulation of Polycomb-associated chromatin has been found in mice and humans with diet-induced obesity (50,51), suggesting that the mechanisms we found here could also underlie the chemosensory alterations reported in mammals (8)(9)(10)(11)(12).…”
Section: Discussionsupporting
confidence: 57%
“…Evidence is emerging that the levels of salt, sugar, and fat in diets can alter taste sensation in humans (3)(4)(5), raising the question of whether these sensory changes may influence food intake, obesity, and metabolic disease (6,7). This idea is supported by a number of recent animal studies that found changes in taste, neural responses, and food preferences in rodents fed high-nutrient diets (8)(9)(10)(11)(12)(13). However, because of the complexity of the mammalian taste system and the lack of genetic tools, we know next to nothing about the molecular mechanisms through which diet composition affects taste sensation and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of diets high in sugar and fat decreases the perception of taste stimuli, influencing food preference and promoting food intake (Bartoshuk et al 2006;Sartor et al 2011;Kaufman et al 2018;Ahart et al 2019;May et al 2019;Weiss et al 2019) . Recent studies have examined the effects of these diets on the sensitivity of the peripheral taste system and the intensity of taste experience (Maliphol, Garth, and Medler 2013;Kaufman et al 2018;May et al 2019;Weiss et al 2019) , but how exactly taste deficits increase feeding behavior is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster fruit flies fed high dietary sugar experience lower sweet taste sensation as a result of the decreased responsiveness of the sweet sensory neurons to sugar stimuli (May et al, 2019a) . Given the importance of sensory cues to control eating, and recent data that diet also impacts taste in mammals (Ahart et al, 2019;Chen et al, 2010;Kaufman et al, 2018;Maliphol et al, 2013;May et al, 2019a;McCluskey et al, 2020;Weiss et al, 2019) , we set out to identify the molecular mechanisms through which the food environment shapes sensory responses. Since sweet taste deficits develop within 2-3 days upon exposure to the high sugar diet and independently of weight gain (May et al, 2019a) , we reasoned that gene regulatory mechanisms may be involved in modulating the responses of the sensory neurons.…”
Section: Prc21 Modulates Sweet Taste In Response To the Food Environmentioning
confidence: 99%
“…We recently found that high dietary sugar dulls the responses of the fruit fly taste neurons to sweet stimuli, causing higher food intake and weight gain (May et al, 2019a(May et al, , 2019b . Mammals fed high nutrient diets also show changes in taste, neural responses, and food preferences (Ahart et al, 2019;Chen et al, 2010;Crow, 2012;Kaufman et al, 2018;Maliphol et al, 2013;May et al, 2019a;McCluskey et al, 2020;Sartor et al, 2011;Weiss et al, 2019) , arguing that the effects of diet on taste are conserved and promote obesity. However, the molecular mechanisms through which the food environment alters taste sensation, and more broadly, neural physiology, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%